Strengthening Religious Character Education Through Community-Based Child-Friendly School Programs - Didik Supriyanto (Future Tecno-Science Publisher, 2025)
This community service activity aims to strengthen religious character education through the implementation of a community-based child-friendly school program. The program was implemented at an elementary school in Mojokerto Regency, involving teachers, parents, and community leaders. The activity methods included teacher training, student mentoring, and community discussion forums. The results of the activity demonstrated increased awareness among teachers and parents of the importance of religious character education, the creation of a safe school environment, and improved religious behavior in students' daily activities. This program is expected to become a model of collaboration between schools, families, and the community in fostering children's religious character.